2011
DOI: 10.2196/jmir.1669
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing Telemedicine Applications: The Challenge of Legitimizing Decision-Making

Abstract: During the last decades a variety of telemedicine applications have been trialed worldwide. However, telemedicine is still an example of major potential benefits that have not been fully attained. Health care regulators are still debating why institutionalizing telemedicine applications on a large scale has been so difficult and why health care professionals are often averse or indifferent to telemedicine applications, thus preventing them from becoming part of everyday clinical routines. We believe that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…Mean costs for the health care system provide another informative measure for policy decisions and confirm that the remote device monitoring might become an institutionalized service [33]. Our analysis showed that the mean annual cost for the management of the patients in the remote arm was €167.23 lower than that in the standard arm (€1962.78 versus €2130.01; P =.80).…”
Section: Discussionsupporting
confidence: 58%
“…Mean costs for the health care system provide another informative measure for policy decisions and confirm that the remote device monitoring might become an institutionalized service [33]. Our analysis showed that the mean annual cost for the management of the patients in the remote arm was €167.23 lower than that in the standard arm (€1962.78 versus €2130.01; P =.80).…”
Section: Discussionsupporting
confidence: 58%
“…The rapid development of worldwide Internet infrastructures has facilitated development of systems in this domain. Telemedicine applications have in particular allowed to introduce new organizational structures in health services 40 and consequently led to an interest in the use of the TAM to facilitate the organizational adaptation. Health care policy makers are still debating why institutionalizing telemedicine applications on a large scale has been so difficult, 53 and why health care professionals are often averse or indifferent to telemedicine applications.…”
Section: Discussionmentioning
confidence: 99%
“…Health care policy makers are still debating why institutionalizing telemedicine applications on a large scale has been so difficult, 53 and why health care professionals are often averse or indifferent to telemedicine applications. 40,54 We believe that user rejection is one of the important factors in institutionalizing various types of telemedicine applications. Therefore, it is important to examine the effective factors in accepting telemedicine applications by health care professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard practice guidelines for the amount of self-management activity and changes to individual care plans based on these readings parallel traditional care; however, the lack of clarity in supporting clinician decision-making may be, in large part, why healthcare professionals are often averse or indifferent to adopting telemedicine applications [19]. Decisions related to the extension of the most promising telemedicine applications are complex and should include multiple stakeholders such as practitioners, healthcare regulators and governments [20]. Key elements for monitoring patients with CRD via telemedicine are shown in figure 3.…”
Section: Chronic Conditions Comorbidity and Telemonitoringmentioning
confidence: 99%